Social and historical transposition in the Hikayat Patani: Julia Kristeva's intertextual analysis - Islahuddin, Islahuddin; Wiyatmi, Wiyatmi; Sayuti, Suminto A. (Universitas Ahmad Dahlan, 2026)
Hikayat Patani is a literary work born from the Patani community that describes its social and historical conditions. This qualitative study examines social and historical transposition in the Hikayat Patani using Julia Kristeva's intertextual approach. The research data source is Hikayat Patani, with data collected through text reading and mapping, systematic recording, and contextual analysis. Data analysis includes suprasegmental and intertextual techniques. The study reveals the following social transpositions: 1) Patani port center; 2) Patani trade center; 3) Patani community is prosperous and prosperous; 4) development of Sungai Tambangan; and 5) treasurer in the government. Historical transpositions include: 1) Patani kingdom of the Islamic sultanate; 2) names of the sultans of Patani; 3) Patani led by a female king; 4) female monarch names; and 5) Patani kingdom maritime kingdom. The research reinforces Kristeva's intertextual theory in Malay literature analysis and underscores the role of Hikayat Patani as a source of history, culture, and Islamization. These findings support the development of local culture-based teaching materials and the strengthening of Patani Malay identity.